The impact of re‐opening the international border on COVID‐19 hospitalisations in Australia: a modelling study. Issue 1 (11th October 2021) - Hanly, Mark J; Churches, Timothy; Fitzgerald, Oisin; Post, Jeffrey J; MacIntyre, C Raina; Jorm, Louisa
Abstract: Objective: To estimate the numbers of COVID‐19‐related hospitalisations in Australia after re‐opening the international border. Design: Population‐level deterministic compartmental epidemic modelling of eight scenarios applying various assumptions regarding SARS‐CoV‐2 transmissibility (baseline R 0 = 3.5 or 7.0), vaccine rollout speed (slow or fast), and scale of border re‐opening (mean of 2500 or 13 000 overseas arrivals per day). Setting: Simulation population size, age structure, and age‐based contact rates based on recent estimates for the Australian population. We assumed that 80% vaccination coverage of people aged 16 years or more was reached in mid‐October 2021 (fast rollout) or early January 2022 (slow rollout). Main outcome measures: Numbers of people admitted to hospital with COVID‐19, December 2021 ‒ December 2022. Results: In scenarios assuming a highly transmissible SARS‐CoV‐2 variant ( R 0 = 7.0), opening the international border on either scale was followed by surges in both infections and hospitalisations that would require public health measures beyond mask wearing and social distancing to avoid overwhelming the health system. Reducing the number of hospitalisations to manageable levels required several cycles of additional social and mobility restrictions. Conclusions: If highly transmissible SARS‐CoV‐2 variants are circulating locally or overseas, large and disruptive COVID‐19 outbreaks will still be possible in Australia after 80% of people aged 16 years or more have been vaccinated. Continuing public health measures to restrict the spread of disease are likely to be necessary throughout 2022.